Adaptive physical education based on a functional-digital approach and football tools for children with intellectual disabilities - Tsukhlov, N.A.; Burtseva, E.V.; Parfenova, L.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to provide a theoretical justification for applying the functional-digital (phygital) approach in the process of adaptive physical education, with an emphasis on creating individualized and motivating conditions for the development of motor and cognitive skills in children with intellectual disabilities and autism spectrum disorder (ASD). Methodology and organization of the study. The study is grounded in the analysis of scientific and methodological literature and regulatory documents, the description of modern digital and interactive technologies (VR, AR, MR) in adaptive physical education, as well as a structured examination of algorithms within digital platforms that implement the principles of adaptability, individualization, visualization, and progress monitoring for children with intellectual disabilities and autism spectrum disorder. Results and conclusions. The implementation of the functional-digital approach in the process of adaptive physical education contributes to the formation of a controlled, personalized, and predictable learning environment for children with intellectual disabilities and autism spectrum disorders. The use of digital technologies such as VR, AR, and MR makes it possible not only to individualize the workload and exercise complexity but also to provide visual support and instant feedback, which enhances motivation, engagement, and the frequency of motor action repetitions. The analysis demonstrates that the use of the functional-digital approach ensures the comprehensive development of physical qualities, cognitive and social skills, contributes to the prevention of secondary disabilities, and provides conditions for safe, gradual, and motivating acquisition of new motor abilities. The digital environment becomes an effective tool for supporting a child along an individual developmental trajectory and facilitating social integration. Overall, the phygital approach in adaptive physical education confirms its high effectiveness and promise for working with children with ID and ASD.